The crystal structure of bis(pyrazolo[1,5-a]pyrimidine-3-carboxylato-κ2N,O)-copper(ii), C14H8N6O4Cu - Hong Dong-Feng; Chen Ye; Zhu Wen-Li (Zeitschrift für Kristallographie - New Crystal Structures)
C14H8N6O4Cu, monoclinic, C2/c (no. 15), a = 15.6054(8) Å, b = 7.0441(3) Å, c = 12.6301(6) Å, β = 108.550(5)°, V = 1316.24(11) Å3, Z = 4, Rgt(F) = 0.0317, wRref(F2) = 0.0778, T = 293 K.